Asteraceae dos campos rupestres da cadeia do espinhaço: distribuição espacial e a influência do ambiente - Nascimento, Lídia Campos (2017)
The Asteraceae family, despite showing a high diversity in the campos rupestres of the EspinhaçoRange, reveals an uneven distribution due to the high environmental heterogeneity found throughout this mountain chain. Hence, the study’s main purpose was to: [1] describe the spatial distribution of Asteraceae; [2] recognize the phytophysiognomic distribution patterns; and [3] identify the key environmental variablesto influence the distribution of this family. Initially, a database was created for the Asteraceae occurring in the campos rupestres of the EspinhaçoRange, using the records drawn from the databases SpeciesLink and Jabot. Moreover, further information provided by the taxonomic revisions of the group, floristic surveys focussing on the Asteraceae, and published descriptions of new species occurring within the studied area were added to this database. Cluster analysis (UPGMA), ordination (NMDS) and canonical analysis (RDA) were performed to explore the data and to investigate the influence of the environmental variables. 19 tribes, 106 genera (17 endemic) and 535 species (179 endemic) of Asteraceae were identified, representing 10.6% of the flora of the campos rupestres of the Espinhaço Range. The highest species richness occurred in the Chapada Diamantina and in the Espinhaço Meridional. A higher share of more species within the phytophysiognies of the cerrado sensu lato was observed. The campos rupestres belonging to the Caatinga (BA) domain constituted a distinct group in relation to those belonging to the Cerrado and Tropical Atlantic domain (MG), owing to differences in precipitation levels and temperature along the Espinhaço Range. Thus, for the purpose of studies conducted at landscape scale, it has to be concluded that the diversity of Asteraceae of the campos rupestres is influenced mainly by climate, whereas for those conducted at local scale, soil geomorphological characteristics are more important